Comparative Study of Structural Behaviour for Rolled and Castellated Steel Beams with Different Strengthening Techniques - Hadeed, Shakir Mahmood; Hussain Alshimmeri, Ahmad Jabbar (Civil Engineering Journal, 2019)
Currently, the castellated steel beams are used widely because of their useful structural applications and serviceable performance due to their good significant properties such as light weight, facility in construction, materials economize and strength. The castellated steel beam fabricated from its origin solid beam (I-beam) by cutting its web in a zigzag path and then re-joined the two halve by welding so the height of the castellated beam expanded about 50%. The aim of this paper is to study the effect of castellation with and without strengthening on the structural behaviour of castellated beams and compare the results with the origin solid steel beam. Three castellated beams with deferent configuration in addition to solid beam subjected to two equal point loads at mid third of span with simple support condition were analysed numerically using finite element analysis by Abaqus software virgin (6.14.5) .The results show that the load carrying capacity values of castellated steel beams that represent (second, third& fourth) models were increased by (39.11,105.95&124.77) % respectively compared with origin solid beamÂ  due to increase beams stiffness after castellation and strengthening process, while mid-span deflection values at service load were decreased by (36.36,9.10&27.27) % respectively comparing with the origin solid steel beam due to increasing section dimensions and stiffness after castellation process and using strengthening technique respectively. Also it was seen that the maximum ultimate moment and ductility were observed in the fourth model that strengthened by high strength concrete and lacing reinforcement so they increased by 124.79% and 165.65% respectively as compare to reference beam, while the third model that strengthened by high strength concrete was stiffer than other beams.